Endoscopic Grading and Sampling of Gastric Precancerous Lesions: A Comprehensive Literature Review. - Tziatzios, Georgios; Ziogas, Dimitrios Ι.; Gkolfakis, Paraskevas; Papadopoulos, Vasilios; Papaefthymiou, Apostolis; Mathou, Nikoletta; Giannakopoulos, Athanasios; Gerasimatos, Gerasimos; Paraskeva, Konstantina D.; Triantafyllou, Konstantinos (Current Oncology, 2024)
Gastric cancer remains a disease with an ominous prognosis, while early gastric cancer has a good-to-excellent prognosis, with 5-year survival rates of up to 92.6% after successful endoscopic resection. In this context, the accurate identification of patients with established gastric precancerous lesions, namely chronic atrophic gastritis and intestinal metaplasia, is the first step in a stepwise approach to minimize cancer risk. Although current guidelines advocate for the execution of random biopsies to stage the extent and severity of gastritis/intestinal metaplasia, modern biopsy protocols are still imperfect as they have limited reproducibility and are susceptible to sampling error. The advent of novel imaging-enhancing modalities, i.e., high-definition with virtual chromoendoscopy (CE), has revolutionized the inspection of gastric mucosa, leading to an endoscopy-based staging strategy for the management of these premalignant changes in the stomach. Nowadays, the incorporation of CE-targeted biopsies in everyday clinical practice offers not only the robust detection of premalignant lesions but also an improvement in quality, by reducing missed diagnoses along with mean biopsies and, thus, the procedural costs and the environmental footprint. In this review, we summarize the recent evidence regarding the endoscopic grading and sampling of gastric precancerous lesions.